DISTRIBUTION OF THE OCCURRENCE OF THE INTENSIVE IONOSPHERE SCINTILLATIONS ON THE OBSERVATIONS OF THE COSMIC RADIO SOURCES AT THE DECAMETER WAVE RANGE - Lytvynenko, O. A.; Panishko, S. K. (Одеські астрономічні публікації, 2020)
Effect of scintillations arises in the result of interaction of radio signal from the cosmic radio source with irregularities of ionosphere plasma which appears at the registration of observations as amplitude fluctuations. Wherein fluctuations of the different intensities and with the different long time periods can be observed. Scintillations of large intensity and with large characteristic times (periods) take an interest because its influence on records of the radio sources is very essential and can distort the record shape. In this case there is a need to consider the presence of the intensive fluctuations. In this sense it might be useful to investigate the frequency of occurrence of the intensive scintillation. Processing of the radio sources records was carried out on the observations of power cosmic radio sources at the passage through direction pattern of the radio telescope URAN-4 at frequencies 20 and 25 MHz during 1998-2007. Record’s characteristics were obtained including ionosphere scintillation parameters. Also records with scintillations of large intensity and with long periods were marked. In this work daily distribution of intensive scintillations was analyzed. It was showed that occurrence of intensive scintillations changes in limits of 4-26% and it is larger on the lower frequency. Dependence of occurrence of scintillations from angle between direction on the radio source and line of geomagnetic field in the observation place was found. It was obtained that the maximum of the occurrence of the intensive scintillations for all observed radio sources appears on the nighttime of the day. Also local maximums of frequency of occurrence are exist which may be associated with the moments of sunrise and sunset